STRUKTUR GARAPAN GANDANG TAMBUA SEBAGAI PERWUJUDAN KEARIFAN LOKAL MASYARAKAT DESA CUBADAK AIA KECAMATAN PARIAMAN UTARA KOTA PARIAMAN - Wahyuni, Irfi Sri; Indrayuda, Indra (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2014)
This article aims to reveal the structure of arrangement of Gandang Tambua and the function of Gandang Tambua in the communities in terms of local wisdom. This study examines the values in local wisdom that are represented in the arrangement of Gandang Tambua in Cubadak Aia village, Pariaman Utara district, Pariaman City. This research is qualitative using descriptive method. Data is collected through interview, observation with direct participation, documentation, and literature review. Data is then analysed according to Miles and Huberman’s. The result shows that the arrangement structure of Gandang Tambua consists of parts related to each other. ‘Tasa’ plays as the main role in leading the performance of Gandang Tambua, while Gandang Tambua follows Tasa. It means, based on the local wisdom, the leaders are one step in front and one level higher. It also refers to the social structure of Minangkabau community where the children see their uncles as kings, the unces see ‘pangulu’ (tribal leaders) as kings, pangulu see the truth as king, and the truth stands on its own. Gandang Tambua also serves as the media for social integration, entertainment, and communication. Keywords: Gandang Tambua, local wisdom, function and structure of arrangement